If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 9x + -24 Reorder the terms: -3 + 2x = 9x + -24 Reorder the terms: -3 + 2x = -24 + 9x Solving -3 + 2x = -24 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 2x + -9x = -24 + 9x + -9x Combine like terms: 2x + -9x = -7x -3 + -7x = -24 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -7x = -24 + 0 -3 + -7x = -24 Add '3' to each side of the equation. -3 + 3 + -7x = -24 + 3 Combine like terms: -3 + 3 = 0 0 + -7x = -24 + 3 -7x = -24 + 3 Combine like terms: -24 + 3 = -21 -7x = -21 Divide each side by '-7'. x = 3 Simplifying x = 3
| 7+9=8u-u | | 5x+29=13x-51 | | x-8=-2 | | x-15=-7 | | x+(-15)=9 | | x+(-11)=5 | | x+13=22 | | x+15=36 | | 12*8=x | | 7=2x(x-4)-3(x-4) | | 14-x=15 | | -6(t-2)-(t+2)=6 | | 7-9x=47-16x | | -121-7x=9x+23 | | 4x+7=-15-7x | | 3x+51=8x+11 | | 126-3x=5x+14 | | -16-2x=8-8x | | (4t-5)=2(t+1)+4 | | 4x+10=80-6x | | 6+3x=22+x | | 2y+4=2(y+2) | | 4x-2=12x-98 | | 8v-3=9v-1 | | 3x+27=13x-53 | | 12x-10=9x+5 | | 5n+6=26 | | 3+7(x-8)=4-7(x-1) | | 3x+5=-(x-13) | | -2(4n+6)=2 | | 3(x-3)-9=0 | | 14y-3=72-y |